ANALISIS ROA, ROE, EPS, PER, DAN DER TERHADAP HARGA SAHAM PADA PERUSAHAAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013–2016 - Mafazah, Charista Nurul (JURNAL AKUNTANSI DAN MANAJEMEN, 2018)
The aim of this research to examine are there impact of ROA, ROE, EPS, PER, and DER as an independent variable whit stock price as dependent variable on 10 real estate companies listed in Indonesia stock exchange and have financial statements in the period 2013–2016 so that the unit of analysis obtained is 40 financial statement list real estate company. The research variable consisted on independent variable in the form of return on asset (X1), return on equity (X2), earning per share (X3), price earning ratio (X4), debt to equity ratio (X5), and stock price (Y) as a dependent variable. Methods of data collection in of this research is the method of documentation. Data analysis technique were use multiple linier regression. Based on the results of regression analysis known that influence of return on asset, return on equity, earning per share, price earning ratio, and debt to equity ratio and simultaneously influence the stock price on the Indonesia stock exchange in period 2013–2016 at 92,8% while the rest influenced by other variables is not examined in this research. Partially, return on asset and earning per share significantly influence to stock prices, while return on equity, price earning ratio, debt to equity ratio but not significant effect on stock prices.